The relationships among nurses’ spiritual health, sleep quality, and stress and the factors influencing stress during the late global COVID-19 pandemic: A cross- sectional study - Yueh-E. Lin; Li-Yu Chien; Mei-Lien Hu (PLoS ONE, 2025)
Background COVID-19 has had a significant impact on healthcare workers. Although several studies have looked at the pandemic’s physical and mental effects on nurses, little has been done to investigate their spiritual health and its relationship to stress and sleep quality during the late pandemic. Purpose This study sought to fill a knowledge gap in the literature about the relationships between nurses’ reported stress, sleep quality, and spiritual health during the late COVID-19 epidemic. Methods A cross-sectional study using purposive sampling was performed out in a medical center in Taiwan. A total of 376 nurses participated. The Perceived Stress Scale, Pittsburgh Sleep Quality Index, and Spiritual Health Scale-Short Form were used for assessing nurses’ stress levels, sleep quality, and spiritual health. Results The results showed that the mean perceived stress score was 1.80 ± 0.50 (out of 4), the sleep quality score was 8.17 ± 3.29 (out of 21), and the mean spiritual health score was 3.66 ± 0.59 points (out of 5). Although 77.1% of the nurses in this study experienced sleep disorders (PSQI > 5), they had better sleep quality during the COVID-19 pandemic than those in other countries. Perceived stress, sleep quality, and spiritual health were significantly correlated. Nurses with support from their friends and family and hospital during the COVID-19 pandemic had lower perceived stress and higher sleep quality and spiritual health scores than their peers (p < .05). Age, work experience, sleep quality, and spiritual health were predictors of perceived stress in nurses during the late COVID-19 pandemic (F = 20.19, p < .001) and could explain 30.6% of the variation. Conclusions Spiritual health is correlated with the nurses’ stress levels. Despite providing extrinsic support, we encourage nursing management to pay attention to nurses’ spiritual needs and implement psychological education programs to help frontline nurses navigate ever-changing and discerning healthcare environments.